PECULIARITIES OF EXERCISING THE RIGHT TO APPLY TO THE COURT FOR REINSTATEMENT CASES IN UZBEKISTAN - Boboraimova Mavluda Mirzakarimovna (Journals Park Publishing, 2023)
This article discusses the origins, implementation, specifics, problems and recommendations of the right to apply to the court for reinstatement, as well as opinions on recent changes in the law.
Keywords: employment contracts, legislation, codes, reinstatement, recovery of wages, settlement agreement, material and moral damage, public contract.